English for specific purposes: Traditions, trends, directions - Mohammad Ali Salmani-Nodoushan (Universitas Syiah Kuala, 2020)
English for Specific Purposes (ESP) began around fifty years ago as a result of pressing worldwide demands for fast-paced language training in occupational and professional settings, rapid revolutions in theoretical linguistics, and burgeoning pressures on schools and educators to focus on, and to be responsive to, learners’ needs. It started within the field of English Language Teaching (ELT) but has gradually established itself as an autonomous subfield of Applied Linguistics (AL). This paper will review the origins, evolution, and status quo of ESP, and then predict the future directions of this important field. The theoretical, analytical, and methodological evolutions of ESP are reviewed, the positions of genre analysis, target language use situation analysis, and context in ESP are described, the ‘just-in-case’ EAP and ‘just-in-time’ EOP approaches are compared, and the text-first and context-first approaches to discourse structure analysis are compared. The paper predicts that ESP will adopt a wide-angled epistemological stance to survey the (a) discursive, (b) generic, (c) social, and (d) organizational structures of specialized texts and discourses, as well as those of texts and discourses simplified for the popularization of science, in a systematic and contextualized manner. ESP practitioners are also warned about the potential threats of teaching genres of power within ESP.